Influence of all-out and fast start on 5-min cycling time trial performance - Aisbett, B.; LeRossignol, P.; Mcconell, G. K.; Abbiss, C. R.; Snow, R. (Medicine & Science in Sports & Exercise, 2009)
Purpose: To examine the influence of two different fast-start pacing strategies on performance and oxygen consumption (VO2) during cycle ergometer time trials lasting ~5 min.